Transformasi Digital dalam Pengelolaan Peraturan Desa : Implementasi dan Dampak Website Badan Permusyawaratan Kalurahan - Dwi Jatmoko; Aci Primartadi; Murhadi Murhadi; Basuki Basuki; Danang Ariwibowo (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
This community service activity aims to develop community services through the website of the Kalurahan Consultative Body. Participants in this activity are members of the Village Consultative Body and Village Leaders. This activity consists of three stages, namely planning, implementation, and evaluation. The method carried out is public service to village regulations and website management workshops. The results of the evaluation showed that the service activities had been carried out well. The participants were enthusiastic and actively participated in this activity. This is shown from the participants' input on the form of the website menu and the results of the evaluation, which shows an increase in public knowledge about the use of the website as a form of village regulation innovation service. With the implementation of this activity, it is hoped that the village regulations can be read and understood by many parties so that people who visit this website can know the village regulations. Especially.